DevOps culture and practice with OpenShift : deliver continuous business value through people, processes, and technology /: deliver continuous business value through people, processes, and technology. (2021) - Beattie, Tim; Hepburn, Mike; (Computer consultant), O'Connor, Noel; Spring, Donal
No abstract available